Pattern of cutaneous adverse drug reactions due to the use of fixed dose drug combinations - MS, Radhika; SS, Mayur; Kop, Priyadarshini (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Fixed dose drug combinations (FDCs) possess a higher risk of causing adverse drug reactions (ADRs) compared to a drug used individually. This study analyzes the pattern of ADRs caused due to the use of FDCs in a tertiary care hospital. Methods: A prospective, spontaneous ADR reporting study was conducted for two years at a tertiary care hospital. ADRs reported due to suspected FDC use were evaluated for causality (WHO-UMC probability scale), severity (adapted Hartwig scale) and avoidability (Modified Hallas J. et al. scale). Results: Of the 29 (96.67%) cutaneous ADRs reported, 19 (63.34%) ADRs were due to irrational FDCs, of which 16 (53.34%) were ‘probable’, 13 (43.34%) were ‘possibly avoidable’ and 13 (43.34%) were ‘mild/level 2’ on the severity scale. Conclusion: Irrational FDCs carry a higher risk of causing cutaneous ADRs. Awareness and regular reporting of such ADRs can help physicians fight the evil of irrational prescribing.